2019
DOI: 10.1139/cjas-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Fibre digestion by rumen microbiota — a review of recent metagenomic and metatranscriptomic studies

Abstract: Plant biomass is the most abundant renewable resource on the planet, and the biopolymers of lignocellulose are the foundation of ruminant production systems. Optimizing the saccharification of lignocellulosic feeds is a crucial step in their bioconversion to ruminant protein. Plant cell walls are chemically heterogeneous structures that have evolved to provide structural support and protection to the plant. Ruminants are the most efficient digesters of lignocellulose due to a rich array of bacteria, archaea, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 63 publications
6
37
0
Order By: Relevance
“…Our analysis of the microbial community of the reindeer rumen of the Nenets Autonomous Okrug practically did not reveal any bacteria of the Fibrobacter genus. In general, this is consistent with the data obtained as a result of the analysis of rumen microbiomes of animals belonging to Cervidae family (reindeer and elk), in which the Fibrobacteres phylum bacteria did not occupy a dominant position compared to cattle, in which this phylum often became dominant [21].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Our analysis of the microbial community of the reindeer rumen of the Nenets Autonomous Okrug practically did not reveal any bacteria of the Fibrobacter genus. In general, this is consistent with the data obtained as a result of the analysis of rumen microbiomes of animals belonging to Cervidae family (reindeer and elk), in which the Fibrobacteres phylum bacteria did not occupy a dominant position compared to cattle, in which this phylum often became dominant [21].…”
Section: Resultssupporting
confidence: 91%
“…Wu et al [20] described a crustal rumen microbiome that included 8 phyla (Bacteroidetes, Firmicutes, Proteobacteria, Spirochaetes, Fibrobacteres, Verrucomicrobia, Synergistetes, and Actinobacteria). However, the vast majority of the microbiome (up to 90%) is occupied by representatives of phyla of Bacteroidetes and Firmicutes [21].…”
Section: Resultsmentioning
confidence: 99%
“…As expected, due to the higher abundance of Firmicutes in the soil termite cluster, the average transcript abundance of cohesin/dockerin and SLH annotated genes was much higher in soil feeders than in plant fibre feeders. It would indicate the active presence of cellulosomes in the former group [51]. Gene transcript taxonomic assignment indicated that enzymes involved in carbohydrate metabolism originated mainly from Firmicutes, Spirochaetes, Fibrobacteres and Bacteroidetes (Additional file 1: Figure S10).…”
Section: Landscape Of Prokaryotic Cazymes In Guts Of Plant Fibreand Smentioning
confidence: 99%
“…As expected, due to the higher abundance of Firmicutes in the soil termite cluster, the average transcript abundance of cohesin/dockerin and SLH annotated genes was much higher in soil feeders than in plant bre feeders. It would indicate the active presence of cellulosomes in the former group [51]. Gene transcripts taxonomic assignment indicated that enzymes involved in carbohydrate metabolism originated mainly from Firmicutes, Spirochaetes, Fibrobacteres and Bacteroidetes (Additional le 1: Figure S10).…”
Section: Landscape Of Prokaryotic Cazymes In Guts Of Plant Breand Soimentioning
confidence: 99%